Nutrigenomics and Atherosclerosis: The Postprandial and Long-Term Effects of Virgin Olive Oil Ingestion - Ortega, Almudena; Varela, Lourdes M.; Bermudez, Beatriz; Lopez, Sergio; Muriana, Francisco J.G.; Abia, Rocio (IntechOpen, 2012)
None